The Impact Between Self-Efficacy and Community Engagement on Psychological Empowerment in a Gender-Focused Tourism Curriculum: Insights from the WTIDcamp 2023 Program - Monica, Anindwitya Rizqi (Gadjah Mada Journal of Tourism Studies, 2024)
In numerous studies, psychological empowerment is considered crucial for assessing the extent to which individuals perceive their ability to shape their roles and overcome job difficulties (Speitzer, 1995). As an industry, tourism stands out as one of the sectors predominantly occupied by women, accounting for as much as 55% (UN Women, 2020), thus frequently utilized as a tool for empowerment by various stakeholders (Staudt, 1990; Scheyvens, 2000; Chevalier, 2023). Consequently, it is intriguing to examine how psychological empowerment is construed by tourism workers. The objective of this research was to investigate the influence of self-efficacy and community engagement on the psychological empowerment of participants in the WTID Camp 2023. WTID Camp 2023 is a program initiated by Women in Tourism Indonesia aimed at raising awareness among tourism students and fresh graduates regarding the importance of gender equality in the Indonesian tourism industry workforce. This study employed quantitative research using multiple linear regression analysis (Sugiyono, 2010), where multiple linear regression aimed to predict the fluctuations in the dependent variable when two or more independent variables were manipulated (increased or decreased in value). There were 56 samples comprising tourism students participating in the WTID Camp 2023, aged between 18 and 24 years. Data were obtained through questionnaires constructed using Likert scales. The results indicate that community engagement significantly influences psychological empowerment. Similarly, self-efficacy significantly influences community engagement. However, self-efficacy does not significantly influence psychological empowerment.